Performance Optimization on Multi-Core Processors and Windows 11 Kernel Management - Putra, Aan Fadillah; Wisnu Ikhwansyah Saputra; Elkin Rilvani (Yayasan Insan Mulia Bima, 2024)
Multi-core processors have become the primary solution to improve processing performance by dividing tasks across multiple processing cores. This study analyzes the performance of two operating systems with the same hardware. Parameters such as boot time, CPU usage, memory efficiency, and application performance are tested through Pass Mark Performance Test and Geekbench. The method used in this study uses a quantitative approach with an experimental method. This approach was chosen to analyze and measure system performance objectively through controlled testing. The test results include boot time, processor workload distribution, memory efficiency, and application responsiveness. The results show that Windows 11 has a faster boot time, a more even distribution of processor workload, and increased memory efficiency. In addition, virtualization-based security (VBS) makes applications more responsive. Therefore, Windows 11 is the best option for high-performance multicore environments.